Biomimicry principles in green building index Malaysia - Hj Mohd Ariffin, Noor Aziah; Gad, Salwa Abdelkarim (2015)
Many countries have initiated consciousness of environmental approaches in the planning and development of the built environment due to concerns about climate change and global warming. These are in the forms of energy rating system indexes, such as, LEED, Breeam, GBI, etc. to create more sustainable buildings and developments that are less harmful to the natural environment. Although good and novel, this paper contends that these ratings are remedying and alleviating whatever negative impacts that development create on the natural environment. The rating systems are seemingly lacking attempts to integrate and enhance the physical development together with the natural environment. On the other hand, Biomimicry is a discipline that explores nature and attempts to understand its bio-integration to allow for the establishment of sustainable products, processes and systems. This paper postulates that with the integration of Biomimicry’s Life Principles (BLP) into the Green Building Index (GBI) Malaysia, a higher level of sustainability upon the natural environment could be achieved. The study utilized the content analysis method to explore the presence and the extent of the presence of Biomimicry frameworks in the existing GBI. This paper concludes that although the presence of BLP in the GBI is high, the extent or level of the presence is low. The paper also recommends the areas of concern that could be improved within the GBI for a more effective and sensitive rating system to make the built environment more sustainable.